Individual foraging variation drives social organization in bottlenose dolphins. (9th September 2019) - Methion, Séverine; Díaz López, Bruno
Abstract: Identifying foraging variation within a population and assessing its relationship with social structure is essential to increase knowledge about the evolution of social systems. Here, we investigated individual foraging variation in bottlenose dolphins and its potential influence on their social organization. We used generalized affiliation indices and applied social network analysis to data collected over four consecutive years of research in a coastal area subject to significant use and pressure by humans. Our findings revealed variation in foraging behavior among individual bottlenose dolphins, which in turn shapes their social organization. Our results indicated that individuals that frequently foraged within human-altered areas (i.e., shellfish farms) exhibited weaker Strength, Reach, and Affinity compared to others. These bottlenose dolphins profit from a reliable and easily located food source, which may increase their energy intake and interindividual competition. In contrast, individuals that foraged less frequently within the shellfish farms occupied a central position within the network and exhibited strong associations. These individuals may benefit from increased cooperation and reduced intragroup competition, thus increasing learning and information sharing, as they may face a patchy and irregular distribution of prey. We also demonstrated that bottlenose dolphins preferred to affiliate with other individuals with similar foraging strategies (i.e., homophily), which could promote, through time, a segregation of the population into behaviorally distinct groups. These findings provide valuable insight into the evolution of bottlenose dolphin social systems and their response to human-induced changes in the marine environment. Lay Summary: We identified variation in foraging behavior among individual bottlenose dolphins, which in turn shapes their social organization. We reveal that bottlenose dolphins that frequently foraged within human-altered areas (i.e., shellfish farms) exhibit weaker associations compared to others, as the reliable and easily located food source may have made less necessary for dolphins to cooperate with conspecifics. Furthermore, our results suggest that bottlenose dolphins preferred to affiliate with other individuals with similar foraging strategies.